The Effect of Ability, Cultural Organization and Motivation on Employee Satisfaction And Performance On Religion Ministry Sragen - Windarto, Arif (STIE AUB Surakarta)
This study aims to identify and analyze the influence of ability, organizational culture and motivation toward the satisfaction and performance of employees at the Ministry of Religious Sragen. This research is quantitative research using SPSS software applications with the analytical techniques used is to use the instrument test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. T test results on the first equation can be concluded that the variables ability, organizational culture and motivation positive and significant impact on job satisfaction. Both the t test in the equation it can be concluded that the ability, organizational culture, motivation and job satisfaction positive and significant effect on performance. Test results F can be concluded jointly variables ability, organizational culture, motivation and job satisfaction affect performance. R2 total value of 0.892 means that the performance of Employees in the Ministry of Religion Sragen explained by variables ability, organizational culture, motivation and job satisfaction amounted to 89.2% and the remaining 10.8% is explained by other variables outside the model study as an example of communication, organizational climate , Results of path analysis showed that: the direct effect on the performance capability variable is greater than the indirect effect through the ability of job satisfaction on performance. So that the variable of job satisfaction as an intervening variable ineffective. Direct influence of organizational culture on performance variables is greater than the indirect effect of organizational culture through job satisfaction on performance. So that the variable of job satisfaction as an intervening variable ineffective. Direct influence on performance motivation variable is greater than the indirect effect of organizational culture through job satisfaction on performance. So that the variable of job satisfaction as an intervening variable ineffective.Â Keywords : Ability, Organizational Culture, Motivation, job satisfaction, employee performance